2013
DOI: 10.1016/j.jbspin.2012.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoids reduce alveolar and trabecular bone in mice

Abstract: Although the amount of alveolar bone is very low in the mouse, this study shows that GCs can induce an alveolar bone loss in long-term treated animals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 40 publications
0
24
0
3
Order By: Relevance
“…The maximum score of 25 was registered for a report on the maxillar bone [35], while a minimum sore of 13 was found in a mandibular study [44]. The median score was 21 and was reached by 11 studies: 1 in the maxilla [6], 6 in the mandible [11], [13], [31], [32], [34], [42] and 4 in the condyle [22], [25], [30], [33].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The maximum score of 25 was registered for a report on the maxillar bone [35], while a minimum sore of 13 was found in a mandibular study [44]. The median score was 21 and was reached by 11 studies: 1 in the maxilla [6], 6 in the mandible [11], [13], [31], [32], [34], [42] and 4 in the condyle [22], [25], [30], [33].…”
Section: Resultsmentioning
confidence: 99%
“…Six studies applied in vivo micro-CT, performed in the maxilla [6], [15], [20], [21] and in the condyle [10], [22]. The scanning device which was most often used was the μCT 40 (Scanco Medical, Brüttisellen, Switzerland) [9], [11], [13], [14], [19], [23], [24], [25], [26], [27], [28], [29], [30], [31], followed by the Skyscan apparatus (Skyscan, Aartselaar, Belgium) [3], [4], [8], [20], [21], [32], [33], [34], [35]. The results of the quantitative analysis are presented in Table 2, Table 3, Table 4.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We observed that GC treated mice had decreased bone volume, bone strength in the distal femur and vertebra, reduced bone formation, and evidence of reduced mineralizing surface and surface based bone formation [17,30,36]. Yao et al reported that GC-induced bone loss is caused by early upregulation of genes involved in osteoclast activation, function, and adipogenesis, followed by a delayed but extended reduction in expression of genes associated with osteoblast activation and maturation [28].…”
Section: Discussionmentioning
confidence: 99%
“…14 Following analyses in vitro, other animal studies have reported that corticosteroids induced bone resorption. 15 A human cross-sectional study evaluating the long-term effects of inhaled corticosteroids reported that corticosteroids might reduce bone remodeling, causing a decrease in bone mineral density. 16 Another side effect associated with taking multiple drugs is xerostomia, which is associated with inflammation and bleeding from periodontal structures.…”
Section: Introductionmentioning
confidence: 99%